Quantitative determination of metaxalone in human plasma by LC-MS and its application in a pharmacokinetic study - Lanting Zhao; Qian Li; Chang Shu; Keli Wang; Li Ding (Elsevier, 2016)
A simple and rapid method using liquid chromatography-mass spectrometry (LC-MS) for the determination of metaxalone in human plasma has been developed and validated. Letrozole was used as the internal standard (IS). The plasma samples were simply treated with acetonitrile which allowed the precipitation of plasma proteins. The chromatographic separation was achieved on a Sapphire C18 (2.1 mm × 150 mm, 5 µm, Newark, USA) column using the mobile phase (5 mM ammonium acetate containing 0.01% formic acid: acetonitrile (45:55, v/v)) at a flow rate of 0.3 ml/min. The selected ion monitoring (SIM) in the positive mode was used for the determination of [M + H]+ m/z 222.1 and 286.1 for metaxalone and letrozole, respectively. The standard curve obtained was linear (r2 ≥ 0.99) over the concentration range of 30.24−5040 ng/ml. Meanwhile, no interfering peaks or matrix effect was observed. The method established was simple and successfully applied to a pharmacokinetic study of metaxalone in healthy Chinese volunteers after a single oral dose administration of 800 mg metaxalone. The main pharmacokinetic parameters of metaxalone were as follow: Cmax, (1664 ± 1208) ng/ml and (2063 ± 907) ng/ml; AUC0−36, (13925 ± 6590) ng/ml h and (18620 ± 5717) ng/ml h; t1/2, (13.6 ± 7.7) h and (20.3 ± 7.7) h for the reference and test tablets, respectively. These pharmacokinetic parameters of metaxalone in healthy Chinese volunteers were reported for the first time.